2004
DOI: 10.1002/masy.200450623
|View full text |Cite
|
Sign up to set email alerts
|

Monolayers of reactive cellulose derivatives

Abstract: Functional cellulose derivatives are very versatile materials for the creation of mono‐ and multilayer systems. Hydrophobic alkyl and trimethylsilyl celluloses form highly ordered Langmuir‐Blodgett multilayers on hydrophobic substrates. Cellulose thiosulfates and methyl thio ethers were self‐assembled on gold and silver surfaces to form hydrophilic monolayers. Cellulose layer systems are capable for chemical transformations under conservation of the structural order. They are suitable platforms for the investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In solid state such as a thin film, stiff CTA chain is expected to control interparticle distance of gold nanoparticles by the molecular length of CTA chains. Regarding selfassembled monolayers of cellulose derivatives which have recently been studied (Wenz et al 2004(Wenz et al , 2005, cellulose-self-assembled gold nanoparticles are expected to be a novel class of cellulosic material since cellulose chains are organized in a radial manner.…”
Section: Introductionmentioning
confidence: 99%
“…In solid state such as a thin film, stiff CTA chain is expected to control interparticle distance of gold nanoparticles by the molecular length of CTA chains. Regarding selfassembled monolayers of cellulose derivatives which have recently been studied (Wenz et al 2004(Wenz et al , 2005, cellulose-self-assembled gold nanoparticles are expected to be a novel class of cellulosic material since cellulose chains are organized in a radial manner.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported on the SAM formation of cellulose thiosulfates and carboxymethylcellullose thiosulfates and thioethers on gold and silver surfaces and demonstrated that cellulose derivatives are superior to other polymers in forming monolayers (Wenz et al 1999(Wenz et al , 2001(Wenz et al , 2004(Wenz et al , 2005Choi et al 2000). Very stable monolayers were formed showing reproducible thicknesses between 1.2 and 2.4 nm depending on the DS of thio groups at the cellulose backbone.…”
Section: Introductionmentioning
confidence: 95%